The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1365-2966.2005.09981.x
|View full text |Cite
|
Sign up to set email alerts
|

The SAURON project--IV. The mass-to-light ratio, the virial mass estimator and the Fundamental Plane of elliptical and lenticular galaxies

Abstract: We investigate the well‐known correlations between the dynamical mass‐to‐light ratio (M/L) and other global observables of elliptical (E) and lenticular (S0) galaxies. We construct two‐integral Jeans and three‐integral Schwarzschild dynamical models for a sample of 25 E/S0 galaxies with SAURON integral‐field stellar kinematics to about one effective (half‐light) radius Re. They have well‐calibrated I‐band Hubble Space Telescope WFPC2 and large‐field ground‐based photometry, accurate surface brightness fluctuat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

124
1,089
9
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 962 publications
(1,223 citation statements)
references
References 132 publications
(245 reference statements)
124
1,089
9
1
Order By: Relevance
“…assumptions are supported by results of realistic simulations carried out by Lablanche et al (2012) and previous works (Cappellari et al 2006;Cappellari 2008) that have shown that the errors introduced by the uncertainty in these quantities are insignificant compared to the errors on the stellar kinematics of our galaxies.…”
Section: Methodssupporting
confidence: 68%
“…assumptions are supported by results of realistic simulations carried out by Lablanche et al (2012) and previous works (Cappellari et al 2006;Cappellari 2008) that have shown that the errors introduced by the uncertainty in these quantities are insignificant compared to the errors on the stellar kinematics of our galaxies.…”
Section: Methodssupporting
confidence: 68%
“…Dynamical modeling using the orbitsuperposition method is considered to be the state-of-theart technique and allows one to recover both the galaxy gravitational potential and the orbital structure with an accuracy of 15% (Thomas et al 2005;Krajnovic et al 2005). Schwarzschild modeling is now widely used for mass measurements of supermassive black holes, for determination of the total mass profile and its decomposition into luminous and dark matter components as well as for constraining the orbital structure (e.g., Gebhardt et al 2003;Cappellari et al 2006; Thomas et al 2007bThomas et al , 2011McConnell et al 2012McConnell et al , 2013Rusli et al 2013). As such an approach only makes sense with high quality observational data allowing the determination of the high order lineof-sight velocity moments (namely, in addition to velocity and projected velocity dispersion also the third and the fourth order Gauss-Hermite moments (e.g., Gerhard 1993;van der Marel and Franx 1993) or better yet the complete line-of-sight velocity distribution), it can only be applied to nearby galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…2, we show the same trends but now as a function of the total mass of the galaxies. We have derived the mass values assuming it approximates to the virial mass derived from the best-fitting M vir − σ relation presented in [1]. The figure displays a trend with λ R such that smaller values are found in more massive galaxies.…”
Section: Core and Cusp Galaxies In The Sauron Samplementioning
confidence: 99%